The challenges of recruitment in clinical trials in developing countries: the Mycetoma Research Centre experience. (23rd January 2021) - Omer, Rowa Fathelrahman; Ahmed, Eiman Siddig; Ali, Buthyna Mamoun; Alhaj, Hana E; Bakhiet, Sahar Mubarak; Mohamed, El Samani Wadaa; Strub-Wourgaft, Nathalie; Fahal, Ahmed Hassan
Abstract: Mycetoma is a chronic disease caused either by fungi (eumycetoma) or bacteria (actinomycetoma). Treatment remains suboptimal and based on personal clinical experience. Recently, the Mycetoma Research Centre (MRC), a WHO Collaborating Centre on mycetoma, began the first-ever double-blind clinical trial. Here, we report the challenges and barriers faced in the recruitment and retention of patients in the MRC experience. Patient recruitment and retention are critical determinants of clinical trial success and yet a substantial number of trials fail to reach their recruitment goals. Recruitment challenges are identified throughout the different stages of the clinical trial, starting from planning, participant screening and intervention, through to retaining participants for the entire study duration. The MRC made efforts to address these challenges to ensure the constant flow of patients. The recruitment committee at the MRC conducted training workshops for the medical staff in the endemic areas, along with regular meetings with health authorities and local leaders. Moreover, telemedicine technology was used to examine patients in endemic areas. Challenges and barriers facing clinical trial conduct need to be examined thoroughly to ensure actionable, evidence-based recommendations for improving patient recruitment and retention. In conclusion, effective patient recruitment and retention are based on three pillars, which are proper clinical trial design and protocol development, realistic and feasible trial site selection, and objective communication with the trial stakeholders.